2018
DOI: 10.1183/13993003.00864-2018
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rates in primary spontaneous pneumothorax: a systematic review and meta-analysis

Abstract: Primary spontaneous pneumothorax (PSP) recurrence rates vary widely in the published literature, with limited data describing the factors that influence recurrence. The aims of this systematic review were to determine an estimation of PSP recurrence rates and describe risk factors for recurrence.A systematic review was conducted of all studies reporting PSP recurrence. Electronic searches were performed to identify English language publications of randomised trials and observational studies. The population was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 48 publications
4
90
0
4
Order By: Relevance
“…How to prevent recurrence of PSP without surgery is unclear. There is a hypothesis that chest tube may irritate the pleural surface and may work like mechanical pleurodesis [14,30,31]. This probably could explain findings in some studies which showed that the recurrence rate after conservative management (without any intervention or only needle aspiration) is higher comparing to chest tube drainage [14,21,22,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How to prevent recurrence of PSP without surgery is unclear. There is a hypothesis that chest tube may irritate the pleural surface and may work like mechanical pleurodesis [14,30,31]. This probably could explain findings in some studies which showed that the recurrence rate after conservative management (without any intervention or only needle aspiration) is higher comparing to chest tube drainage [14,21,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…The recent large systematic review and meta-analysis on PSP recurrence after nonsurgical management (conservative management, needle aspiration, chest tube drainage) showed that the estimated recurrence rate was 32% and varied from 8% up to 74% [30]. The risk of PSP recurrence after chest tube drainage is up to 42% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of PSP is based on two principles: first, the initial management of the pneumothorax with symptom control and re-expansion of the lung and secondly, reducing recurrence rate [4]. The recurrence rate is reported to be between 17 and 54% [5][6], with the majority of recurrences in the first year after the primary event [7]. Recurrence rate can be reduced by surgical pleurectomy or thoracoscopic pleurodesis [8].…”
mentioning
confidence: 99%
“…Recurrence rate can be reduced by surgical pleurectomy or thoracoscopic pleurodesis [8]. Initial management of PSP has been subject of ongoing debate [4,8], with a trend towards a more conservative approach using manual aspiration and outpatient treatment [4,6,[8][9][10][11][12]. Manual aspiration has been shown to be effective in approximately two-thirds of patients [8] and is as equally effective as chest tube drainage [8].…”
mentioning
confidence: 99%